2023
DOI: 10.1007/s11440-023-01920-6
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the combined effect of initial density and temperature on the soil–water characteristic curve of unsaturated soils

Abstract: The soil–water characteristic curve (SWCC) plays an important role in solving the stability and deformation problems of unsaturated soils. In many practical situations, soils are usually experienced by both deformations and thermal conditions. In this interest, the paper proposes a simple and effective model to predict the combined effect of initial density and temperature on the SWCC and to be able to quantify the changes in thermal-hydro-mechanical behavior of unsaturated soils. In the first step, an initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…However, significant variations in soil density can be introduced by external factors and stress conditions of the soils. This intricacy highlights how crucial it is to investigate how density affects the SWCC, making it an engaging and extensively researched topic of broad interest [32][33][34][35][36]. Chen et al [29] found that higher initial dry density led to increased water retention capacity.…”
Section: Introductionmentioning
confidence: 99%
“…However, significant variations in soil density can be introduced by external factors and stress conditions of the soils. This intricacy highlights how crucial it is to investigate how density affects the SWCC, making it an engaging and extensively researched topic of broad interest [32][33][34][35][36]. Chen et al [29] found that higher initial dry density led to increased water retention capacity.…”
Section: Introductionmentioning
confidence: 99%
“…However, it does not provide a complete explanation of the temperature-influence mechanism of the SWRC. Numerous studies have demonstrated that as soil temperature increases, additional variables, including soil air retention, the thermal expansion of water, alterations in the soil-water contact angle, and modifications to the soil pore distribution, also contribute to variations in soil hydraulic properties [16][17][18][19]. However, the investigation of temperature on soil hydraulic characteristics in the Benggang area is limited.…”
Section: Introductionmentioning
confidence: 99%